The Concerns of Nation-State Sovereignty and International Commercial Law: A Path to Harmonisation - Tran Vang-Phu; Duong Anh Son (Khazanah Hukum, 2024)
The current body of literature on international business and commercial laws demonstrates the inherent conflict between the legal system and the sovereignty of nation-states. The phenomenon of globalization has amplified the influence of non-state actors, regional organizations, and free trade agreements, resulting in a significant demand for international arbitration. The incorporation of international commercial laws into the current standard is increasingly prevalent, as nation-states discover the benefits of adhering to such laws. Conversely, the concept of national sovereignty, which exerted significant influence in recent years, appears to be facing substantial challenges due to the emerging trends in an increasingly interconnected globalized world. Nevertheless, the nation-state and its sovereignty maintain a significant impact on the dynamics of power and trade between different nation-states. This study undertakes an examination of the substantial discord between principles of international commercial law and the sovereignty attributed to nation-states, with specific attention directed towards the prospects of achieving harmonization. Moreover, it delves into the intricacies and challenges inherent in the pursuit of harmonization within this specific domain.